JUSTIFICATION OF THE ESSENCE, FUNCTIONS AND PURPOSE OF GRAIN FUTURE EXCHANGE MARKET OF AGRICULTURAL PRODUCTS (International Journal of Innovative Technologies in Economy, 2021)
In the article analyzes the development of the domestic stock market. It is substantiated that crop futures are a derivative financial instrument on the stock exchange, which provides for the obligation of its seller or buyer to periodically transfer sums of money to the opposite party depending on changes in the market price of grain, and (or) the obligation delivery of grain on time. It is determined that only under the conditions of joint efforts on the part of the state, the exchange community, participants of the agrarian market that will allow bringing the exchange commodity market closer to civilized bases.